The Types of Business Risk Identified in Integrated Reporting - Chłapek, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The paper presents the possibilities of identifying business risk on the basis of data disclosed in integrated reporting. The research method used relies on a review of Polish and foreign literatures and an empirical analysis of integrated reports disclosed in 2016. The structure of the reports, which complies with the most recent trends and international recommendations with regard to integrated reporting, confirms the hypothesis put forward in the paper. The concluding remarks aim to arouse interest in research on the possibilities of verifying and assessing disclosures related to the identification of risk in integrated reporting.